2022
DOI: 10.1038/s41598-022-05183-1
|View full text |Cite
|
Sign up to set email alerts
|

Essential function of adaptor protein Nck1 in platelet-derived growth factor receptor signaling in human lens epithelial cells

Abstract: Binding of platelet-derived growth factor-BB (PDGF-BB) to its cognate receptor (PDGFR) promotes lens epithelial cell (LEC) proliferation and migration. After cataract surgery, these LEC behaviors have been proposed as an influential cause of posterior capsule opacification (PCO). Stimulated PDFGR undergoes dimerization and tyrosine phosphorylation providing docking sites for a SH2-domain-containing noncatalytic region of tyrosine kinase (Nck). Nck is an adaptor protein acting as a linker of the proximal and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…PDGFbb, a member of the PDGF family, is involved in various physiological processes, such as mitosis, differentiation, chemotaxis and angiogenesis ( Wang et al, 2019 ). Within the eye, PDGFbb promotes the proliferation of LECs, thus acting as a safeguard against cataract development that may result from a decline in LECs ( Li et al, 2019 ; Paensuwan et al, 2022 ). Moreover, previous studies have reported elevated levels of VEGF in cataract patients ( Mitrović et al, 2016 ), which is inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFbb, a member of the PDGF family, is involved in various physiological processes, such as mitosis, differentiation, chemotaxis and angiogenesis ( Wang et al, 2019 ). Within the eye, PDGFbb promotes the proliferation of LECs, thus acting as a safeguard against cataract development that may result from a decline in LECs ( Li et al, 2019 ; Paensuwan et al, 2022 ). Moreover, previous studies have reported elevated levels of VEGF in cataract patients ( Mitrović et al, 2016 ), which is inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, EMT alters the adhesion, polarity and differentiation of epithelial cells and renders them more prone to migration and invasion [ 10 , 11 , 12 ]. The noncatalytic region of tyrosine kinase 1 (NCK1) is an adaptor protein acting as a linker of the proximal and downstream signaling events that are related to the occurrence and development of a variety of tumors [ 13 , 14 ]. NCK1 upregulation promotes the development of ovarian carcinoma (OC) [ 15 , 16 ], colorectal cancer (CoC) [ 17 ] and cervical squamous cell carcinoma [ 18 ].…”
Section: Introductionmentioning
confidence: 99%